Toponimi Nama-Nama Desa Di Kecamatan Bangun Purba Kabupaten Deli Serdang: Kajian - Latifah Anum; Mhd Isman (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
Toponymy is a science that has an object of study about toponyms in general and about geographical names in particular. The purpose of this study was to find out the toponym or origin of village names in the Bangun Purau subdistrict, Deli Regency, Serdang, for anthropolinguistic studies. The method used in this study is a qualitative descriptive method. Source of data In this study, the source of data used a snowball approach (Snowball Sample), namely the determination of informants based on initial informant references. The data analysis technique is to collect data directly from the results of interviews by informants which are then analyzed based on toponymy aspects according to Surdayat's theory. The results of the analysis carried out can draw the conclusion that there is a toponymy of village names in the Bangun ancient sub-district, Deli district, Serdang anthropolinguistic studies.